Influence of Framing Information and Disposition Effect in Decision of Investment: Experimental Study on Investor Behavior at Indonesia Stock Exchange Representative on Denpasar, Bali - Candraningrat, Ica Rika; Salim, Ubud; Indrawati, Nur Khusniyah; Ratnawati, Kusuma (International Review of Management and Marketing, 2018)
This study aims to examine framing information, disposition effect and interaction between the two on investment decisions made by investors by predicting stock prices. This study uses 2 Ã— 2 between subject experimental design. Participants amounted to 80 individual investors listed as investors in securities companies in Denpasar, Bali. This study involved 80 individual investors of Bali local community based on nonprobability sampling method with purposive sampling technique. Participants were grouped into 4 experimental groups according to a combination of manipulations.The results showed some important findings. First, information framing is one factor that determines investor behavior in making investment decisions. Positively and negatively framed information will lead to different decision-making patterns. Investors who are given a positive information framing will predict stock prices higher than investors given negative information framing. Secondly, this study confirms that information received by investors contributes to the maximum effect of disposition, furthermore the effect of this disposition is influenced by the framing of information received. Third, the interaction between groups of participants who were given different information framing showed a real difference, except the group of participants given negative information indicating the existence of cognitive style differences which are psychological dimensions that represent the consistency of individuals in collecting and processing information and in decision making. This study also proves that there is no difference in behavior in making investment decisions based on gender and investment experience whereas there is a difference in the level of participants’ education. Unique results were found in women participants who had different attitudes toward risk and benefit. Overall participants are posttraditional Balinese people who keep the wisdom of local Balinese culture but are in touch with global culture through stock investment. Keywords: Framing, Disposition Effect, Behavior Finance, Investment Decision JEL Classification: M